Mythopoetical symbolism in the inner form of soviet Ukrainian sensational fiction texts - Yermolenko, S.S. (Мовознавство, 2019)
The article is a case study of the role of mythopoetical linguistic-cultural code elements within the semantic structure of thriller text inner form, carried out with specific reference to Ukrainian Soviet author Vadym Sobko’s trilogy «Starry wings». It argues that the linguistic presentation of the latter’s text-internal world and plot line is largely influenced by traditional mythic symbolism of nature cycles.